Strategies for increasing effective coverage of hypertension services in health care facilities: a scoping review - Djasri, Hanevi; Alfajri, Novi Zain; Asdary, Rahma Novita; Wardoyo, Muhammad Hardhantyo Puspo (BKM Public Health and Community Medicine, 2024)
Purpose: To identify supporting and inhibiting factors for effective coverage of hypertension services, as well as recommendations for improvement efforts that can be made. Methods: A scoping review consists of five steps: Identification of research questions, identification of relevant research articles, study selection, data collection, and data synthesis. Results: 19 articles met the research objectives. Supporting factors include information systems, electronic-based pharmaceutical services, self-management, health insurance, quality improvement cycles, support for professionals, patients’ interventions, and digital technology. Inhibiting factors include low health insurance coverage, inaccurate equipment, inappropriate diagnosis and treatment, lack of screening coverage, difficulty in access, and differences in policies and procedures between regions. Recommendations for improvement include changes to service systems, the use of defined hypertension thresholds, ensuring blood pressure measurement devices are functioning properly, and the implementation of consistent policies, systems, and processes throughout the healthcare system, including between regions. Conclusion: There are various opportunities for improvement, both in utilizing existing supportive factors and reducing inhibiting factors, as well as in implementing various improvement recommendations, especially those that proved effective in published research.